The transformative dance of the crisis to resignify social educational work: auto-ethnographical reflections on a cooperative enquiry in Northern Italy during the COVID-19 pandemic - Antonella Cuppari (European Journal for Research on the Education and Learning of Adults)
This contribution proposes an autoethnographic reflection on a cooperative enquiry involving social workers, volunteers and family members of people with intellectual disabilities in Northern Italy. The author, a social worker and doctoral student, recognises the complexity of her own positioning and reflects on the educational work that takes place in the social sphere, on the risks connected to a technocratic logic and on critical, and transformative possibilities offered by the crisis. The author proposes a systemic reflexivity that challenges the dominant discourses, connects the micro, meso and macro levels and promotes different ways of knowing. The dynamism of the body, linked to the author's experience in the field of contemporary dance, becomes a symbolic way to decolonise the posture of social workers and open it up to the transformative potential of a sensitive, conscious and incorporated social educational work.